2006
DOI: 10.1345/aph.1g561
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotic–Induced Akathisia with Depression: Therapeutic Role of Mirtazapine

Abstract: Mirtazapine is efficacious in treating atypical antipsychotic-induced akathisia. It may be a good option, particularly in patients with coexisting depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“… 101 Comparative studies have shown cyproheptadine, zolmitriptan, and vitamin B6 produce similar levels of DRBA-A symptom reduction when compared with a range of doses (40–120 mg/day) of propranolol. 102 – 104 Serotonin 5-HT 2A receptor antagonists, such as mirtazapine, 105 110 trazodone, 111 fluvoxamine, 112 zolmitriptan, 103 mianserin, 113 and cyproheptadine, 102 represent another class of treatments for DRBA-A. 114 Blocking this receptor likely plays a role in reducing symptoms by increasing downstream dopamine signaling in areas of the brain affected by DRBAs.…”
Section: Discussionmentioning
confidence: 99%
“… 101 Comparative studies have shown cyproheptadine, zolmitriptan, and vitamin B6 produce similar levels of DRBA-A symptom reduction when compared with a range of doses (40–120 mg/day) of propranolol. 102 – 104 Serotonin 5-HT 2A receptor antagonists, such as mirtazapine, 105 110 trazodone, 111 fluvoxamine, 112 zolmitriptan, 103 mianserin, 113 and cyproheptadine, 102 represent another class of treatments for DRBA-A. 114 Blocking this receptor likely plays a role in reducing symptoms by increasing downstream dopamine signaling in areas of the brain affected by DRBAs.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement was noted after 2–7 days, and only case 3 could be weaned off mirtazapine over a month without recurrence, whereas case 1 could be maintained on 3.75 mg dose. In another case series ( n = 5), Ranjan and colleagues reported reduction in AIAA with the addition of 15 mg mirtazapine, with an additional benefit for depressive symptoms [Ranjan et al . 2006].…”
Section: Resultsmentioning
confidence: 99%
“…Both the Poyurovsky studies were also identified through a PUBMED search [Poyurovsky et al 2003[Poyurovsky et al , 2006. Four studies were excluded as they were case reports or case series [Poyurovsky and Weizman, 2001a;Wilson, 2005;Ranjan et al 2006;Poyurovsky et al 2014]. In a case study, Poyurovsky and Weizman observed a reduction of AIAA (that did not improve with trial of biperiden 4 mg twice daily for 5 days, and subsequently diazepam 10 mg for 3 days) after the second day, with the addition of a morning dose of 15 mg mirtazapine [Poyurovsky and Weizman, 2001a].…”
Section: Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies7,17) mentioned that mirtazapine is efficacious in treating atypical antipsychotic (olanzapine, risperidone, aripiprazole)-induced akathisia, particularly in patients with coexisting depression. This discrepancy with our study may be due to the presence of comorbid depression in patients (our study excluded clinically depressive patients).…”
Section: Discussionmentioning
confidence: 99%